CHARACTERISTIC FEATURES OF MULTIPLE ORGAN FAILURE IN CASES OF PERITONEAL SEPSIS - Ivashchuk, L. Yu.; Pizhitsky, I. B. (International Journal of Medicine and Medical Research, 2017)
Background. The study of hystomorphology of liver and small intestine in experimental peritonitis is presented. Due to this information the criterion of pathogenetic moment transition SIRS for peritoneal sepsis was determined. Objective. The aim of the research was to study the morphology of terminal part of small intestine and liver in cases of experimental peritonitis. Methods. For histological and electron microscope study the biopsy of liver, small intestine were taken; the samples were stabilized in a neutral formalin, dried in alcohol of increasing concentration and placed in paraffin. Paraffin sections were painted with hematoxylin and eosin and studied under the light-optical microscope. Results. Apoptosis caused damage to enterocytes and hepatocytes of first bacterial translocation. Mechanism of vasodilatation effect of NO and its effect on apoptosis were determined. Septic shock was accompaniment of two main levels of body cells damage: apoptosis and membranes destruction. Peritoneal sepsis is a grave condition caused by progressive peritonitis and polyorgan insufficiency syndrome. The phases of peritonealis sepsis pathogenesis were defined. Conclusions. The presented morphological criteria prove the initiation of apoptosis within 24 hours after the development of peritonitis in enterocytes and hepatocytes.